1983
DOI: 10.1139/v83-231
|View full text |Cite
|
Sign up to set email alerts
|

Methanation of carbon monoxide and dioxide by supported metal carbonyl clusters

Abstract: The catalysis of carbon monoxide hydrogenation by supported cobalt and ruthenium clusters is studied, and an unusually specific cobalt methanation catalyst is described. A variety of ruthenium carbonyl clusters catalyzes carbon monoxide methanation, irrespective of support, and Ru3(CO)12 on γ-alumina is found to be a potentially useful carbon dioxide methanation catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…mechanism, these data suggest that the reversible substitution of a chloride ligand on PtCl42" by alcohol must occur prior to reduction of PtCl42". /3-Hydride elimination would ultimately lead to formation of Pt°and the carbonyl product; this has been directly observed for the reaction of (PPh3)2 PtCl2 with alcohol.15 HOCHR,R2 + PtCl42" z=£ PtCl3OCHR,R22" + CL - Pt°+ 20" + 2HC1 + R,C(=0)R2 (2) The stoichiometry of reaction 2 is supported by a 94% yield of acetone when a 4 mM solution of K2PtCl4 with 1 equiv of 2-propanol in H20 reacts under dark conditions. The necessity of a proton on the -carbon is demonstrated by a lack of reactivity when ferf-butyl alcohol is employed as the reducing agent.…”
Section: Resultsmentioning
confidence: 80%
“…mechanism, these data suggest that the reversible substitution of a chloride ligand on PtCl42" by alcohol must occur prior to reduction of PtCl42". /3-Hydride elimination would ultimately lead to formation of Pt°and the carbonyl product; this has been directly observed for the reaction of (PPh3)2 PtCl2 with alcohol.15 HOCHR,R2 + PtCl42" z=£ PtCl3OCHR,R22" + CL - Pt°+ 20" + 2HC1 + R,C(=0)R2 (2) The stoichiometry of reaction 2 is supported by a 94% yield of acetone when a 4 mM solution of K2PtCl4 with 1 equiv of 2-propanol in H20 reacts under dark conditions. The necessity of a proton on the -carbon is demonstrated by a lack of reactivity when ferf-butyl alcohol is employed as the reducing agent.…”
Section: Resultsmentioning
confidence: 80%
“…Anchoring RuCl 3 by impregnation on inorganic supports was reported in several instances to result in a catalyst for the reaction. More recently, it was shown that the use of ruthenium dodecacarbonyl in place of the mononuclear complex enhanced not only the conversion of C0 2 , but also the selectivity toward CH,, production (14,15). Fur thermore, these cluster derived catalysts were found to have longer life and to give better conversion to methane at lower temperatures than their mononuclear counter parts.…”
Section: Diffuse Reflectance Cellmentioning
confidence: 99%
“…But, due to the activation barrier for reducing CO to CH 4 by hydrogen, methanation kinetics is favored at high temperatures. The temperature range of catalytic methanation is reported to be around 200-400°C, depending on the composition and properties of catalyst [7][8][9]. The traditional methanation catalyst is Ni supported on alumina (Al 2 O 3 ) [10].…”
Section: Introductionmentioning
confidence: 99%